Iron Melodies From Kusumodilagan: An Exploration - Sugiyanto, Sugiyanto; Aris Setiawan (Jurnal Seni Musik, 2024)
Kusumodilagan is an area renowned for its iron market, where the livelihoods of the community predominantly rely on iron processing. The various types of iron produced reflect the character of individuals within the society, along with the accompanying phenomena and challenges. Community activities, characterized by the sounds of iron work, have served as a source of inspiration for musical creation. This study aims to explore how to develop a musical presentation that encapsulates the lives of iron workers in Kusumodilagan. The methodology employed in this research is participatory observation, which seeks to understand and recognize the diverse sound characteristics and their social phenomena as the primary approach in the preparation of musical compositions. The findings indicate that the sounds of iron can serve as a compositional idea for musical harmony, while also engaging iron workers in the creative process. The objective of this study extends beyond artistic experience; it emphasizes the recognition of community members' existence and fosters a sense of togetherness among them.